Sex differences in anthropometrics and heading kinematics among Division I soccer athletes. A pilot study - Bretzin, A. C.; Mansell, J. L.; Tierney, R. T.; McDevitt, J. K. (Sports Health: A Multidisciplinary Approach, 2017)
Soccer players head the ball repetitively throughout their careers; this is also a potential mechanism for a concussion. Although not all soccer headers result in a concussion, these subconcussive impacts may impart acceleration, deceleration, and rotational forces on the brain, leaving structural and functional deficits. Stronger neck musculature may reduce head-neck segment kinematics. Hypothesis: The relationship between anthropometrics and soccer heading kinematics will not differ between sexes. The relationship between anthropometrics and soccer heading kinematics will not differ between ball speeds. Study Design: Pilot, cross-sectional design. Level of Evidence: Level 3. Methods: Division I soccer athletes (5 male, 8 female) were assessed for head-neck anthropometric and neck strength measurements in 6 directions (ie, flexion, extension, right and left lateral flexions and rotations). Participants headed the ball 10 times (25 or 40 mph) while wearing an accelerometer secured to their head. Kinematic measurements (ie, linear acceleration and rotational velocity) were recorded at 2 ball speeds. Results: Sex differences were observed in neck girth (t = 5.09, P < 0.001), flexor and left lateral flexor strength (t = 3.006, P = 0.012 and t = 4.182, P = 0.002, respectively), and rotational velocity at both speeds (t = -2.628, P = 0.024 and t = -2.227, P = 0.048). Neck girth had negative correlations with both linear acceleration (r = -0.599, P = 0.031) and rotational velocity at both speeds (r = -0.551, P = 0.012 and r = -0.652, P = 0.016). Also, stronger muscle groups had lower linear accelerations at both speeds (P < 0.05). Conclusion: There was a significant relationship between anthropometrics and soccer heading kinematics for sex and ball speeds.